2009
DOI: 10.1007/s11240-009-9546-6
|View full text |Cite
|
Sign up to set email alerts
|

In vitro regeneration of the important North American oak species Quercus alba, Quercus bicolor and Quercus rubra

Abstract: North American oak species, with their characteristic strong episodic seasonal shoot growth, are highly problematic for clonal micropropagation, resulting in the inability to achieve a stabilized shoot multiplication stage. The potential for initiating and proliferating shoot cultures derived from Quercus alba, Q. bicolor and Q. rubra explants was investigated, and a micropropagation method for these species was developed. Branch segments from 6 to 7-year-old trees were forced-flushed and the forced shoots wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
1
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 46 publications
3
68
1
8
Order By: Relevance
“…Nodal sub-culturing in micro-shoot proliferation, which has been successful for some hardwoods and herbaceous plants, many species of oak (Vieitez et al 2009), Bixa orellana (Parimalan et al 2011), Senecio cruentus (Sivanesan and Jeong 2012), and Piper longum (Rani and Dantu 2012), was also effective with N. cadamba in the present study (data not shown).…”
Section: Discussionsupporting
confidence: 53%
“…Nodal sub-culturing in micro-shoot proliferation, which has been successful for some hardwoods and herbaceous plants, many species of oak (Vieitez et al 2009), Bixa orellana (Parimalan et al 2011), Senecio cruentus (Sivanesan and Jeong 2012), and Piper longum (Rani and Dantu 2012), was also effective with N. cadamba in the present study (data not shown).…”
Section: Discussionsupporting
confidence: 53%
“…VIEITEZ et al (2009), contudo, para Bauhinia cheilantha, nas concentrações de 0; 1,0 e 2,0 g L -1 de carvão ativado testadas, não se observaram efeito favorável para a variável em análise, independentemente da concentração de regulador utilizada (GUTIÉRREZ et al, 2011 O desenvolvimento do sistema radicular a partir da formação de raízes adventícias, em plantas propagadas vegetativamente sob condições in vitro ou in vivo, é um processo de grande complexidade e envolve diversos fatores que ainda não estão completamente elucidados (SOUZA & PEREIRA, 2007). Com isso, é necessário fazer outros estudos adicionando outros reguladores de crescimento associados ao carvão ativado para comprovar qual a melhor inte-ração para promover o enraizamento in vitro.…”
Section: Resultsunclassified
“…Los resultados aquí encontrados coinciden con los reportados por Poornima y Ravishankar (2007), quienes encontraron que el CA fue más eficaz que el PVP en la disminución de la exudación fenólica en Psidium guajava L. Estos autores también observaron que 60 % de los explantes sembrados en el medio de cultivo MS, suplementado con PVP, mostró oxidación después de 30 días de incubación. En encino, la aplicación de 3 mg·L -1 de AgNO 3 disminuyó el necrosamiento y la senescencia temprana de explantes de hojas durante la etapa de iniciación (Vieitez et al, 2009). Los efectos deletéreos en P. pinaster, debido a los fenoles, también fueron reducidos por la adición de CA en el medio de cultivo como lo señala Lelu-Walter et al (2006) y Álvarez et al (2009), quienes sugieren que este resultado puede atribuirse a la propiedad higroscópica del compuesto en el medio de iniciación.…”
Section: Resultados Y Discusión Evaluación De Antioxidantesunclassified
“…There are studies that describe micropropagation protocols of P. pinaster based on organogenesis and somatic embryogenesis, using culture methods that contain both growth regulators and antioxidants (Álvarez et al, 2009). Various antioxidants have been applied in the culture medium to reduce tissue necrosis during the initiation stage of the explants extracted from woody species (Aliyu, 2005;Nomura, Matsumoto, Masuda & Inoue, 1998;Poornima & Ravishankar, 2007;Vieitez et al, 2009. In pecan micropropagation different types of tissue of the plant have been used (Rodríguez & Wetzstein, 1994), as well as somatic embryos (Long, Preece & Sambeeck, 1995).…”
Section: E Mbryogenic and Organogenic Responses In Pecan (Carya Illinmentioning
confidence: 99%
See 1 more Smart Citation